Gasping the death throes: a case report and review of literature on salmonella empyema among malignancy patients - Mohd Taib, Niazlin; Sither Joseph Vesudian, Narcisse Mary; Ahmad Zaidi, Irda Yuhanis; Zainuddin, Nurnabilah; Mohd Ali, Marlindawati (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2024)
Salmonella infection typically manifests as gastroenteritis and enteric fever. The detection of Salmonella in empyema is rare, predominantly occurring in immunocompromised individuals. We report the case of a 68-year-old male with underlying lung adenocarcinoma who presented to the Emergency Department (ED) with right-sided pleural effusion. Pleural fluid aspiration was performed, and microbiological analysis of the sample identified the organism as Salmonella enterica serotype Kalamu (S. Kalamu). The patient was treated with parenteral amoxicillin-clavulanate for a total duration of five weeks. This case aims to highlight the potential role of non-typhoidal Salmonella (NTS) as a causative agent of pleural empyema, thereby enhancing clinical awareness and its implications in patient management, particularly in individuals with underlying malignancies.